Lightering company unloading freight from a scow on the beach, Nome, approximately 1901 - Nowell, Frank H., 1864-1950 (1901)
Caption on image: Nowell, 24. Sesnon Co. Lightering Freight at Nome, Alaska To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number